COMPARATIVE ANALYSIS OF STAGED VERSUS INDEX PROCEDURE COMPLETE REVASCULARIZATION IN ST-ELEVATION MYOCARDIAL INFARCTION - SHAH , SB; KHAN , S (Biological and Clinical Sciences Research Journal, 2024)
ST-elevation myocardial infarction (STEMI) is a critical condition that necessitates quick and efficient revascularization techniques. Recently, there has been a discussion on the best method for revascularization staged versus index procedure complete revascularization. The study compares the clinical outcomes of staged versus index procedure complete revascularization in ST-elevation myocardial infarction. This study is a prospective comparative analysis conducted at Ayub Teaching Hospital, Abbottabad. The patients were divided into two groups, with 40 participants in each group. Demographic data that included Smoking history, Diabetes mellitus, Dyslipidemia, Previous MI, and (LVEF) was recorded. Intraoperative and postoperative outcomes at 72 hours and six months were recorded. The quality of life was also assessed using SF-36 16. Data was entered and analyzed using SPSS (Statistical Package for the Social Sciences) version 24. P-values of ≤0.05 will be considered statistically significant. These findings suggest that in Group A, the frequency of "No reflow" (1 case) and "Abrupt closure" (0 instances) p=0.02) compared to Group B, where "No reflow" was observed in 2 cases and "Abrupt closure" in 1 case, (and (p=0.01), the investigation into post-operative outcomes, revealed no statistically significant differences between the two groups. P values ranged from 0.31 to 0.45, indicating comparable outcomes. After six months post-surgery, Group A demonstrated significantly better outcomes across various health-related domains than Group B, as indicated by the SF-36 questionnaire. In conclusion, index complete vascularization holds a distinct advantage over staged procedures. The observed differences across various health indicators highlight the potential clinical significance of prioritizing complete revascularization during the initial intervention.